Investigation of the Inherent Variability of the Mediterranean Sea Under Contrasting Extreme Climatic Conditions - Sampatakaki, Angeliki; Zervakis, Vassilis; Mamoutos, Ioannis; Tragou, Elina; Gogou, Alexandra; Triantaphyllou, Maria; Skliris, Nikolaos (Frontiers in Marine Science, 2021)
The internal variability of the Mediterranean Sea’s thermohaline circulation is examined under contrasting extreme thermal and mass atmospheric forcing conditions. Three millennium-long numerical simulation experiments were performed: (a) under current climatology, (b) a strong buoyancy forcing scenario, under cold and dry conditions resembling the Younger Dryas event and (c) a weak buoyancy forcing scenario, under S1a sapropel deposition-like conditions (warm and wet). To isolate the inherent variability of the system, independent of interannual atmospheric forcing variability, the latter was defined as a perpetual year pertinent to each experiment. After an initial spin-up period, self-diagnosed heat and salt fluxes, consistent to sea-surface characteristics, forced a millennium-long, relaxation-free numerical simulation. The inherent spatiotemporal variability of the Mediterranean is analyzed using Empirical Orthogonal Function (EOF) and spectral analysis on the simulated density fields. Our results reveal that the Mediterranean Sea exhibits high sensitivity to climatic conditions, allowing its circulation to alternate from anti-estuarine (for the strong buoyancy forcing scenario, leading to buoyancy loss to the atmosphere) to estuarine (for the weak buoyancy forcing scenarion, corresponding to buoyancy gain from the atmosphere). In all three experiments interannual and decennial variability dominates at upper depth layers and the decennial variability dominates at Gibraltar and Sicily Straits, as well. The first two EOF modes in the deep layers under current conditions express only 60% of the basins’ oscillations, while under the more extreme conditions they correspond to more than 90% of the spatial variability. Moreover, although the first EOF modes of reference and weak buoyancy gain scenarios show that the deep layers of the Mediterranean vary in phase (mainly centennial and intercentennial timescales, respectively), under the strong buoyancy forcing scenario the upper and deeper layers are shown to exchange density (mainly inter-centennial timescale). The second EOF mode of deep waters under both extreme scenarios showed that the western and eastern basins exchange buoyancy in decennial (for the cold/dry) and interdecennial (for the warm/humid) timescales. The deep-water residence time for the Eastern Mediterranean was centennial for the Current period, semi centennial for the strong buoyancy forcing case and intercentennial for the weak buoyancy forcing case.